2009
DOI: 10.1083/jcb.200903070
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy pathway intersects with HIV-1 biosynthesis and regulates viral yields in macrophages

Abstract: Autophagy is a cytoplasmic degradative pathway that can participate in biosynthetic processes, as in the yeast Cvt pathway, but is more commonly known for its functions in removing damaged or surplus organelles and macromolecular complexes. Here, we find that autophagy intersects with human immunodeficiency virus (HIV) biogenesis, mirroring the above dichotomy. Early, nondegradative stages of autophagy promoted HIV yields. HIV Gag-derived proteins colocalized and interacted with the autophagy factor LC3, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
440
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 449 publications
(467 citation statements)
references
References 81 publications
24
440
2
1
Order By: Relevance
“…Autophagy plays a positive role in the replication of Brucella abortus and may assist in HIV biogenesis. 21,22 Moreover, induction of autophagy correlates with an increased Leishmania parasite load. 23 Focusing on the latter one, we could already show that the virulent Leishmania inoculum consists partially of apoptotic-like parasites, through which disease development can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy plays a positive role in the replication of Brucella abortus and may assist in HIV biogenesis. 21,22 Moreover, induction of autophagy correlates with an increased Leishmania parasite load. 23 Focusing on the latter one, we could already show that the virulent Leishmania inoculum consists partially of apoptotic-like parasites, through which disease development can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Some viruses have evolved mechanisms to subvert autophagic machinery to facilitate replication in macrophages. It has been demonstrated that replication of human immunodeficiency virus 1 (HIV-1) was severely impaired in macrophages treated with the autophagy inhibitor 3-methyladenine (3-MA) and in Beclin 1 or Atg7 siRNA-transfected cells (Kyei et al, 2009). Moreover, pharmacological induction of autophagy by rapamycin enhanced yields of virus released from macrophages (Kyei et al, 2009).…”
Section: Induction Of Formation Of Autophagosomes In Bmdms By Ectv Inmentioning
confidence: 99%
“…It has been demonstrated that replication of human immunodeficiency virus 1 (HIV-1) was severely impaired in macrophages treated with the autophagy inhibitor 3-methyladenine (3-MA) and in Beclin 1 or Atg7 siRNA-transfected cells (Kyei et al, 2009). Moreover, pharmacological induction of autophagy by rapamycin enhanced yields of virus released from macrophages (Kyei et al, 2009). On the contrary, Campbell and Spector (2012) found that vitamin D could inhibit HIV-1 replication in macrophages through autophagy induction, and treatment of cells with bafilomycin A (BFA, an inhibitor of the lysosomal vacuolar-ATPase) and knockdown of Beclin 1 and Atg5 counteracted the inhibitory effect of vitamin D. Because autophagy is involved in many biological functions, the exact role of autophagy in ECTV infection should be clarified in future studies.…”
Section: Induction Of Formation Of Autophagosomes In Bmdms By Ectv Inmentioning
confidence: 99%
“…Fluorescence confocal microscopy was performed as described previously (Kyei et al, 2009). Images were acquired using a microscope (META; Carl Zeiss) equipped with a 63×/1.4 NA oil objective, camera (LSM META; Carl Zeiss), and AIM software (Carl Zeiss).…”
Section: Fluorescence Confocal Microscopymentioning
confidence: 99%
“…The reagents used were Ultrapure LPS (InvivoGen), IFN-γ (PeproTech), Cytotoxic LDH assay (Promega), and TO-PRO-3 Iodide (Life Technologies). Immunoblotting and immunostaining were conducted as previously described (Kyei et al, 2009). FAM-YVAD-FMK stainings (FLICA; ImmunoChemistry Technologies) were performed according to the manufacturer's instructions.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%